(3eONd JWHjbj eYGUQs - (3UdGM GdOjf eMeO(B, (3YHO GdHGbjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3GdeONd Edi GdehGQO GdHTQjI,Jchjf hJOQjH GdehGQO GdHTQjI,JOQjH hJfejI GdehGQO GdHTQjI,JYhjV GdehGQO GdHTQjI hEOGQI GdeQJHGJ hGdCLhQ,Jbjje COGA GdehGQO GdHTQjI hJQbjJgG hfbdgG,GdJMOjGJ GdeYGUQI dEOGQI GdehGQO GdHTQjIs
Keywords: (3EOGQI GdCaQGOs; (3GdGLhQs; (3Gdbhj GdYGedI(B-(3JOQjHs